A history of Christian theology : an introduction - Placher, William C. (William Carl), 1948-2008.; Nelson, Derek R. (Louisville, KY : Westminster John Knox Press, 2013)
"A modern classic, A History of Christian Theology offers a concise yet complete chronicle of the whole of Christian theology, from its background in the history of Israel to the liberation and postliberal theologies of recent years. This updated thirtieth anniversary edition includes expanded treatments of theological developments at the end of the twentieth century, and preliminary trajectories for theology in the twenty-first century. It also includes updated bibliographies and revised chapters on important innovations in biblical studies, and their impact on theology. This updated and revised edition will continue to aid the work of both students and faculty for years to come"--
Introduction -- The hope of Israel -- The mission to the Gentiles -- The beginnings of orthodoxy -- An alliance with philosophy -- Truly human, truly divine -- Light in the East -- Augustine -- The path to salvation -- The fragile synthesis -- The absolute power of God -- Faith alone, scripture alone -- The Catholic Reformation -- God's governance -- Reason and enthusiasm -- The city on a hill -- The claims of history -- The end of Western Christendom -- The current scene.
Includes bibliographical references (pages 275-300) and index.
Keywords: Theology, Doctrinal -- History; RELIGION / Christian Theology / History; RELIGION / Christian Theology / General; Theology, Doctrinal; History